The synthesis of soft rocks based on physical and mechanical properties of red mudstone. (March 2022) - Cui, Guangjun; Zhou, Cuiying; Liu, Zhen; Xia, Chang; Zhang, Lihai
Abstract: Although similarity simulation experiments have been widely used in geotechnical engineering, their application in soft rock mechanics is still limited due to the complex water–rock interaction of such rocks. The purpose of this study was to synthesise red mudstone–like materials by the method of mineral composition and proportion are completely similar to that of natural rock samples, using sodium silicate content, compression time and vertical stress to investigate the mechanical properties and composition of soft rocks. The physical and mechanical properties of the synthetic red mudstone–like materials were compared with those of natural red mudstone by the density, acoustic characteristics, and microstructure investigation as well as uniaxial and triaxial compression tests. The results show that the synthetic red mudstone–like materials can reproduce the physical and mechanical properties of natural red mudstone. They show that sodium silicate content is one of the most important factors governing mechanical properties, such as internal friction angle, of the synthetic red mudstone–like materials. Importantly, the synthesis method developed in this study could potentially be widely implemented in rock mechanics and engineering. Highlights: Combination of cementation and compaction is considered in the synthesis method. Red mudstone soft rock which is sensitive to mechanics and water is synthesised. Red mudstone–like materials are similar to natural rock in minerals and properties. The synthetic method can be used to obtain soft rocks with certain properties.